Data Activism di Masa Pandemi: Peran dan Tantangan Lapor Covid-19 dalam Advokasi dan Pengawasan Kebijakan Penanganan Covid-19 di Indonesia - Najib Zahro'u (Sanata Dharma University, 2022)
This article wants to look at the role of the Lapor Covid-19 platform in expanding civic engagement at a time when Indonesian’s government was focused on handling the pandemic. This platform was a response to policies for handling the pandemic in Indonesia, especially those related with data. Lapor Covid-19 actually has a multi-sectoral role; including monitoring pandemic policies, advocating for the rights of health workers, demands for transparency of pandemic data, and providing alternative data related to Covid-19 in the field to the government. This article will try to review the extent to which all activities carried out by Lapor Covid-19 can influence central government policies when handling a pandemic. This article was compiled using the data analysis method that comes from the release of the Lapor Covid-19 document, data that enters the platform channel, interviews with health workers and from other digital sources. All data will be analyzed within the framework of the theoretical framework of data activism in the Global South. The result is the success of Lapor Covid-19 in providing recommendations on policies for handling the pandemic in Indonesia, but it still finds ‘fragility’ that make the movement less effective, such as hacking on various platform channels, the government's resistance to the data that is offered, the un-massive socialization of the Lapor Covid-19, as well as the global political situation related to the imbalance in the handling of the pandemic.